A Nucleosomal Region Important for Ensuring Proper Interactions Between the Transcription Elongation Factor Spt16 and Transcribed Genes in Saccharomyces cerevisiae - Nguyen, Hoai-Trang T. (Genetics Society of America, 2013)
The highly conserved FACT (FAcilitates Chromatin Transactions) histone chaperone assists in the transcription elongation process first by facilitating the removal of histones in front of transcribing RNA polymerase II (Pol II) and then by contributing to nucleosome reassembly in the wake of Pol II passage. Whereas it is well established that FACT localizes across actively transcribed genes, the mechanisms that regulate FACT recruitment to and disengagement from chromatin during transcription still remain to be elucidated. Using the Saccharomyces cerevisiae model system, we previously showed that a histone H3 mutant—H3-L61W—greatly perturbs interactions between the yeast FACT (yFACT) complex and chromatin during transcription, resulting in a pronounced shift in yFACT occupancy toward the 3′ ends of transcribed genes. In the present study we report that two histone H4 mutants—H4-R36A and H4-K31E—alter the association pattern of the yFACT subunit Spt16 across transcribed genes in a fashion similar to that seen for H3-L61W. Interestingly, H4-R36, H4-K31, and H3-L61 are in close proximity to each other on the side of the nucleosome. We also provide evidence that the H4-R36A and H3-L61W mutants impair proper Spt16−chromatin interactions by perturbing a common process. Collectively, our results suggest that a nucleosomal region encompassing the H4-R36, H4-K31, and H3-L61 residues plays an important role in ensuring proper association of yFACT across transcribed genes.